La fuerza obligatoria del Contrato - Ghestin, Jacques (2015)
The author begins this article focusing on how historically the contract has reached such binding; from its philosophical origins, through his word to a matter of loyalty to Christian morality; to attribute the quality of certainty as contribution to the economy and become an indispensable legal instrument of forecasting for relations between individuals. Finally, in the second part of this article, essential applications mainly include contract between both parties and to third parties, also seeking the role of judge.